2019
DOI: 10.1155/2019/5176410
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transport-Enhanced Phase Separation in Porous Media Using a Lattice-Boltzmann Method

Abstract: Phase separation of formation fluids in the subsurface introduces hydrodynamic perturbations which are critical for mass and energy transport of geofluids. Here, we present pore-scale lattice-Boltzmann simulations to investigate the hydrodynamical response of a porous system to the emergence of non-wetting droplets under background hydraulic gradients. A wide parameter space of capillary number and fluid saturation is explored to characterize the droplet evolution, the droplet size and shape distribution, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…However, at high-density ratios (low reduced temperatures), the results have a significant deviation from the analytical solutions with the implementation of the forcing schemes in the standard form. By employing the β-modification in the forcing schemes, the density values obtained by the present numerical simulations are in good agreement with those obtained by the analytical solution in a wide range of reduced temperatures (3) The results presented in this study show that with applying the CS EoS for simulation of considered two-phase flow problems at high-density ratios, the spurious velocity is significantly decreased in the flowfield. This result demonstrates that the CS EoS is more realistic and efficient than SC EoS for simulation of two-phase flows at high-density ratios due to producing less spurious currents at the interfacial region (4) It is shown that the MRT-EDM with the improved forcing scheme produces minimum spurious currents among the other methods.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, at high-density ratios (low reduced temperatures), the results have a significant deviation from the analytical solutions with the implementation of the forcing schemes in the standard form. By employing the β-modification in the forcing schemes, the density values obtained by the present numerical simulations are in good agreement with those obtained by the analytical solution in a wide range of reduced temperatures (3) The results presented in this study show that with applying the CS EoS for simulation of considered two-phase flow problems at high-density ratios, the spurious velocity is significantly decreased in the flowfield. This result demonstrates that the CS EoS is more realistic and efficient than SC EoS for simulation of two-phase flows at high-density ratios due to producing less spurious currents at the interfacial region (4) It is shown that the MRT-EDM with the improved forcing scheme produces minimum spurious currents among the other methods.…”
Section: Discussionsupporting
confidence: 82%
“…where f a ðx, tÞ is the particle distribution function which demonstrates the distribution of particles with the velocity e a in position x at time t. The lattice speed c = Δx/Δt is the ratio of the lattice space Δx to the time step Δt, and τ is the relaxation time which is related to the kinematic viscosity ν = c 2 s ðτ − 0:5ΔtÞ [3]. The subscript a indicates the discrete velocity directions.…”
Section: Srt-and Mrt-lbm Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of these MD simulations will offer a validation between the MD simulations and the continuum Navier−Stokes equations (fluid mass balance and momentum balance for LNAPL and groundwater) with a surface-tensionparametrized force term. The two-phase Navier−Stokes equations can be computed using lattice Boltzmann methods 63 or the volume of fluid methods. 64 The second step is to conduct MD simulations of the effect of PFAS on the established two-phase interface in the first step.…”
Section: Microscale Marangoni Effects As Depicted Inmentioning
confidence: 99%
“…(2) Validation with 4D Experiments. Challenges should also be focused on validation of numerical predictions [6] on pore-scale processes using wellcontrolled laboratory experiments [7,8]. It has been extremely difficult to visualize 3D time-series (i.e., 4D) data during laboratory experiments that investigate reactive transport through a porous and/or fractured medium at sufficient spatial and temporal resolutions, because the processes of interest occur (deep) inside the medium of interest.…”
Section: Next Challengesmentioning
confidence: 99%